2021
DOI: 10.3390/brainsci11111507
|View full text |Cite
|
Sign up to set email alerts
|

Automated Analysis of the Two-Minute Walk Test in Clinical Practice Using Accelerometer Data

Abstract: One of the core problems for people with multiple sclerosis (pwMS) is the impairment of their ability to walk, which can be severely restrictive in everyday life. Therefore, monitoring of ambulatory function is of great importance to be able to effectively counteract disease progression. An extensive gait analysis, such as the Dresden protocol for multidimensional walking assessment, covers several facets of walking impairment including a 2-min walk test, in which the distance taken by the patient in two minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Furthermore, using D i , 43.9% of the 2MWDs exhibit an error ε of less than 5%. Previous studies found similar errors for 2MWTs performed at hospital, with 48.4% of pwMS exhibiting measurement errors of less than 5% [28]. Other studies examining the accuracy and precision of wearable motion sensors reported even lower errors, but their primary limitation is that the walk tests were conducted on a motorized treadmill [29,30].…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, using D i , 43.9% of the 2MWDs exhibit an error ε of less than 5%. Previous studies found similar errors for 2MWTs performed at hospital, with 48.4% of pwMS exhibiting measurement errors of less than 5% [28]. Other studies examining the accuracy and precision of wearable motion sensors reported even lower errors, but their primary limitation is that the walk tests were conducted on a motorized treadmill [29,30].…”
Section: Discussionmentioning
confidence: 90%
“…In addition, rotation at the end of a gait is insufficiently detected because the reversal angle of the odometer is different. A digitized approach with the use of Inertial Measurement Units (IMUs) is increasingly being considered to avoid high inter-rater reliability and to increase the efficiency and accuracy of the measurement process [ 13 , 14 ]. We want to take this approach even further and develop and optimize an automated system for distance measurement by using ML technologies based on the aggregated multidimensional data of PwMS from the MLS.…”
Section: Introductionmentioning
confidence: 99%
“…The strength of this solution is the integration of hand motor testing, gait tests, as well as cognitive and affective assessment under highest regulatory standards. With a special focus on gait testing, Trentzsch et al developed a digitally assisted measurement system that uses accelerometers and multiple algorithms to assess the distance of a 2-min walk test [ 5 ]. The benefit of such a system is the simultaneous realization of standardization as well as objectification of measurement, which can be applied independently of human resources.…”
mentioning
confidence: 99%